(untitled) (Bangladesh Journal of Medical Education, 2026)
Background: Global prevalence of childhood overweight and obesity increased in past 33 years. In Bangladesh, prevalence of childhood overweight and obesity increased five times in last two decades. Objective: To assess and identify different socio-demographic and behavioral factors of childhood overweight and obesity among 5-10 years old children in a school of Dhaka City, Bangladesh. Methods: This was a cross sectional survey followed by a case control study carried out in Institute of Epidemiology Disease Control and Research (IEDCR) during July 2017 to June 2018. We randomly recruited 146 overweight and obese children and 151 normal weight children aged 5-10 years old. Their mothers were interviewed face-to-face using a pretested semi-structured questionnaire. Portable stadiometre and bathroom scales were used for anthropometric measurement. Odds ratios and 95% confidence intervals were calculated for risk factors. Results: The proportion of overweight and obese children was 23% and 22% respectively. The proportion of overweight (24%vs 22%) and obese (25%vs 18%) children were higher among boys than girls (50% vs 40%). The children who ate fast food (OR=3.75; 95% CI: 1.50-10.63), ate snacks more than three times a day (OR=3.3; 95% CI: 1.4-8.7), didn’t participate in sports, fitness or recreational activities at school (OR=2.4; 95% CI: 1.3-4.4) or at home (OR=4.1; 95% CI: 2.1-8.5), and spent daily >2 hours on sedentary activities (OR=1.7; 95% CI: 1.0-2.8) had a higher risk of being overweight or obese. Conclusions: The proportions of overweight and obese children were high among school children. The school authority and the parents should promote more a healthy lifestyle by raising awareness of the benefits of physical activities, games and sports and eating healthy foods at home or school to reduce the burden of childhood overweight and obesity. BJME: Vol.-17, Issue-02, July, 2026: 56-68